Tapgram (Tufts Archival Research Center, 2007)
Philip Morris Tapgram providing an update of political developments important to the tobacco industry. Discusses opposition to and mobilization against new proposed Civil Aeronautics Board regulations restricting smoking on airlines. Offers update on growing grassroots lobbying forces. Addresses developments in Oregon and New York as well as pro tobacco resolutions.